Radiosensibility of Vibrio cholerae o1 incorporated in oysters, to 60CO - Moraes, Ivany R de; Del Mastro, Nélida L; Jakabi, Miyoko; Gelli, Dilma S (Revista de Saúde Pública, 2000)
OBJECTIVE: Evaluate the effect of ionizing irradiation by 60Co on Vibrio cholerae O1, El-Tor, Ogawa, non-toxigenic, incorporated in live oysters Crassostrea brasiliana. METHODS: Samples of oysters were selected from Cananéia town in the South coast of S. Paulo state, Brazil, contaminated with Vibrio cholerae and irradiated with 60Co at 0.5 and 1.0 kGy dosages. RESULTS: Showed significant reductions of the initial number of V. cholerae , ranging from 3.4 x10(7) to 10³ and 10², respectively. The D10 values related with the respective doses of irradiation were 0.173 and 0.235. CONCLUSION: Considering a 6 value as safety factor, it is concluded that 1.41 kGy irradiation dosage is necessary to eliminate a high number of V. cholerae viable cells in oysters. Controls were used in the experiment.